Marketing Strategy Competitiveness in Sidoarjo Private Vocational Training Institutions: Strategi Pemasaran Daya Saing Lembaga Pelatihan Kerja Swasta Sidoarjo - Anita Ariyani; Yusril Ihza M; Gatot Suryono; Imelda Dian Rachmawati (Procedia of Social Sciences and Humanities, 2026)
General Background: The proliferation of post-secondary educational institutions across Indonesia has intensified institutional rivalry, compelling managers to prioritize strategic planning. Specific Background: Private Vocational Training Institutions (LPK) in Sidoarjo face significant pressure to maintain student enrollment numbers in a crowded educational market. Knowledge Gap: While marketing concepts are well-established, empirical evidence regarding the specific application of integrated marketing mix strategies within the context of private vocational training in Sidoarjo remains limited. Aims: This research examines how marketing strategies strengthen institutional competitiveness and evaluates the application of these strategies at LPK LP3I Sidoarjo. Results: Utilizing qualitative case study methods with marketing mix analysis, the findings demonstrate that the systematic implementation of product, price, place, promotion, people, physical evidence, and process strategies directly fosters institutional competitiveness and market endurance. Novelty: This study provides a localized perspective on applying the 7P marketing mix to stabilize enrollment during post-pandemic recovery for vocational training providers. Implications: Educational managers are advised to adopt year-quarter based marketing planning, professional branding through digital channels, and service-oriented human resource development to ensure organizational sustainability and long-term competitiveness. Highlights: Strategic marketing mix integration serves as the cornerstone for institutional market survival in Sidoarjo. Professional branding combined with localized digital outreach maintains relevance in a competitive educational landscape. Human resource development and facility investment provide critical advantages in attracting and retaining prospective trainees. Keywords: Marketing Strategy, Competitiveness, Educational Institutions, Marketing Mix, Vocational Training